Descentralização na gestão pública da educação básica no Peru: as características da implementação do plano piloto e seus efeitos em La Molina e Imperial (2006-2011) - Vera Rojas, Haydeé Liliana (2019)
The present investigation problematized the decentralization of the management of public education in Peru, particularly in the Regular Basic Education (EBR), within the framework of the validity of the Municipalization Pilot Plan, in the period 2006-2011. The general objective of the research is to analyze the decentralization of management and its effectiveness in the validity of the Municipalization Pilot Plan in the districts of La Molina and Imperial Cañete, exploring the relations between decentralization and modernization. To guide the study methodologically, they were assumed as analytical categories: management, decentralization and modernization, considering them as important interpretive keys for understanding the object in a contextualized way and, so to speak, exploring the socio-historical, political and pedagogical dimensions that the (the object) encloses. The investigation used as a central procedure the analysis of documents, taking as sources official documents, whether printed or digital, as well as newspapers. In addition, informal dialogue was also used with people acting on the official bodies, who gave clues about the location of documents and commented on the topic of interest. The data collected and interpreted allowed the verification that the application of decentralization in Peru was complex and suffered the effects of the long centralist tradition of the country. The lack of political and social consensus on the objectives to be achieved, in addition to the fragile citizen participation, showed barriers to the Pilot Plan for the Municipalization of Education (2006-2011), especially for localities with scarce resources, as was the case of Imperial. Thus, Peru continued to struggle to implement decentralization and overcome the great differences between the schools of the capital and the provinces, the city and the countryside. In this way, this research found that the Pilot Plan for the Municipalization of Education projected a decentralizing view of all State services, with the purpose that resources could be used more efficiently, effectively and close to the population, without However, it maintained improbable conditions for the achievement of the proposed objectives, since it lacked technical capacity, human resources and the participation of other social actors, which marked a line full of obstacles to its proper development.